Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.inorgchem.2c00739
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Electro-Reduction of Carbon Dioxide to Methanol Catalyzed by Cobalt Phthalocyanine

Abstract: Density functional theory (DFT) calculations have been conducted to investigate the mechanism of cobalt(II) tetraamino phthalocyanine (CoPc-NH 2 ) catalyzed electro-reduction of CO 2 . Computational results show that the catalytically active species 1 ( 4 [Co II (H 4 L)] 0 ) is formed by a four-electron-four-proton reduction of the initial catalyst CoPc-NH 2 . Complex 1 can attack CO 2 after a one-electron reduction to give a [Co III −CO 2 2− ] − intermediate, followed by a protonation and a one-electron reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 107 publications
5
23
0
Order By: Relevance
“…The detailed reaction mechanism for the transformation of CO 2 to CH 4 is displayed in Figures , , and . Meanwhile, to accurately estimate the barriers for the reduction of 3 to 4 and Int3 to Int5 , the Marcus theory (eq ) was used to calculate the corresponding reorganization energy and thus to obtain the related energy barrier . It is found that for the reduction of 3 to 4 , the reorganization energy and the related barrier are estimated to be +18.4 and +9.0 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed reaction mechanism for the transformation of CO 2 to CH 4 is displayed in Figures , , and . Meanwhile, to accurately estimate the barriers for the reduction of 3 to 4 and Int3 to Int5 , the Marcus theory (eq ) was used to calculate the corresponding reorganization energy and thus to obtain the related energy barrier . It is found that for the reduction of 3 to 4 , the reorganization energy and the related barrier are estimated to be +18.4 and +9.0 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, to accurately estimate the barriers for the reduction of 3 to 4 and Int3 to Int5, the Marcus theory 129 (eq 9) was used to calculate the corresponding reorganization energy and thus to obtain the related energy barrier. 130 It is found that for the reduction of 3 to 4, the reorganization energy and the related barrier are estimated to be +18.4 and +9.0 kcal/mol, respectively. Likewise, for the reduction of Int3 to Int5, the reorganization energy and the related barrier are +7.6 and +13.9 kcal/mol, respectively.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…mechanism of MeOH formation in the PEC reaction is likely to be the same as in electrocatalytic CO 2 reduction, and that CO is the key intermediate to the formation of MeOH. [17,[26][27][28] The optimal potential for FE MeOH of STA-GO/CoPc is about 0.4 V lower than that of CFP-GO/CoPc (Figure 4c), demonstrating the photovoltage contribution from the Si to the catalyst. The lower optimal FE MeOH on STA-GO/CoPc compared with CFP-GO/CoPc may be due in part to the planar structure of the Si substrate; that is, the planar electrode is not able to trap the electrogenerated CO intermediate near its surface for further reduction as effectively as the porous CFP electrode.…”
Section: Methodsmentioning
confidence: 99%
“…At −0.62 V, STA‐GO/CoPc produces MeOH with a TOF of 0.18 s −1 , which is similar to the TOF for MeOH of CFP‐GO/CoPc at −1.0 V measured to be 0.21 s −1 . We propose that the mechanism of MeOH formation in the PEC reaction is likely to be the same as in electrocatalytic CO 2 reduction, and that CO is the key intermediate to the formation of MeOH [17, 26–28] . The optimal potential for FE MeOH of STA‐GO/CoPc is about 0.4 V lower than that of CFP‐GO/CoPc (Figure 4c), demonstrating the photovoltage contribution from the Si to the catalyst.…”
Section: Figurementioning
confidence: 88%
“…Chemie Zuschriften mechanism of MeOH formation in the PEC reaction is likely to be the same as in electrocatalytic CO 2 reduction, and that CO is the key intermediate to the formation of MeOH. [17,[26][27][28] The optimal potential for FE MeOH of STA-GO/CoPc is about 0.4 V lower than that of CFP-GO/CoPc (Figure 4c), demonstrating the photovoltage contribution from the Si to the catalyst. The lower optimal FE MeOH on STA-GO/CoPc compared with CFP-GO/CoPc may be due in part to the planar structure of the Si substrate; that is, the planar electrode is not able to trap the electrogenerated CO intermediate near its surface for further reduction as effectively as the porous CFP electrode.…”
Section: Methodsmentioning
confidence: 99%